WORLD MUSLIMAH SEBAGAI BUDAYA POPULER DALAM BINGKAI MEDIA ONLINE ISLAM - Izziya Putri Ananda (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
World Muslimah is a beauty contest set up by Eka Shanty and aimed as a forum for women in veil to join the beauty queens contest, especially by highlighting the side of spiritualism in women. However, the contest attracts criticism from online media, one of them is arrahmah.com, which is one of the popular online Islamic media with high number of visitors. This research aims to know the framing of arrahmah.com media against the World Muslimah beauty contest. The authors use Pan and Kosicki framing theory to analyze the media ideology to the construction of the reality that is raised. Methodically, this article is a qualitative study based on literature research. From this research, it can be seen from the media perspective through the subjective side of the author, which states that this a beauty contest event is not taught in Islam and women who follow the event is considered to have taken off her side of virtuousness.